Decomposition kinetics of iron (III)-diclofenac compound - Kobelnik, M. [UNESP]; Bernabe, Giseli Aparecida [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Capela, Jorge Manual Vieira [UNESP]; Fertonani, Fernando Luís [UNESP] (Springer, 2009)
Non-isothermal decomposition of iron (III)-diclofenac anhydrous salt was investigated by thermogravimetry (TG) under different conditions in opened and closed alpha-alumina pans under nitrogen atmosphere. To estimate the activation energy of decomposition, the Capela and Ribeiro isoconversional method was applied. The results show that due to the lid cover different activation energies were obtained. From these curves a tendency can be seen where the plots maintain the same profile for closed lids and almost run parallel to each other. Independently of the different experimental conditions no remarkably different results have been obtained.
Keywords: Iron(III)-diclofenac; Thermal decomposition; Non-isothermal; Activation energy